Association of Five Snps in Cytotoxic T-Lymphocyte Antigen 4 and Cancer Susceptibility: Evidence from 67 Studies - Fang, Min; Huang, Wencheng; Mo, Dan; Zhao, Wei; Huang, Rongyong (Cellular physiology and biochemistry, 2018)
Background/Aims: CTLA-4 polymorphisms are associated with susceptibility to various cancers, but the results are often conflicting. Hence, we performed a comprehensive meta-analysis to quantitatively investigate the association between CTLA-4 polymorphisms (rs231775, rs4553808，rs5742909, rs3087243 or rs733618) and cancer risk. Methods: Data were collected from PubMed and Web of Science. A total of 67 case-control studies were selected for quantitative analysis. Stata (Version 12) software was used to calculate the odds ratio (OR) and 95% confidence interval (CI) to evaluate the strength of the associations. Subgroup meta-analysis was conducted based on ethnicity and cancer type. Heterogeneity tests, sensitivity analysis, and publication bias assessments were also performed. Results: rs231775, rs4553808 and rs5742909 but not rs3087243 and rs733618 were significantly related to cancer risk. In analyses stratified by ethnicity, both rs231775 and rs4553808 were significant susceptibility polymorphisms in an Asian population but not in a Caucasian population. Moreover, there were stronger associations between the rs231775 polymorphism and increased risk of bone, breast, liver, head and neck and pancreatic cancers. Additionally, rs4553808 was associated with significantly increased susceptibility to breast cancer and head and neck cancer. Conclusion: rs231775, rs4553808 and rs5742909 may be used as predictive genetic biomarkers for cancer predisposition. Combined detection of CTLA-4 SNPs could be a useful tool for prediction of cancer susceptibility in clinical practice.